2019
DOI: 10.1016/j.scitotenv.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Determining landscape-level drivers of variability for over fifty soil chemical elements

Abstract: • 53 soil chemical elements from 9830 samples covering 39,000 km 2 in southeast China were analyzed. • Longitude, pH, MAT, and MAP strongly affected soil element concentrations. • Topsoil elements have structural and functional thresholds of climate and soil pH. • The thresholds of topsoil elements response to climate were MAP = 1000-1500 mm, MAT = 17.8-18.0°a nd pH = 5.0-5.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…Across three levels, soil pH and BD were found to be negatively related to habitat quality, while soil TN was positively correlated with habitat quality (Figure S4). Those sensitive soil quality indicators (e.g., soil pH, TN, and BD) adjusted plant nutrient absorption, soil element dissolution, and microbial community diversity, which jointly regulate ecosystem function and stability [64][65][66][67]. BRT models showed that MAT had the most considerable contribution to the habitat quality in high-level zones, which largely support previous findings [40].…”
Section: Drivers Of Habitat Quality Patternssupporting
confidence: 81%
See 1 more Smart Citation
“…Across three levels, soil pH and BD were found to be negatively related to habitat quality, while soil TN was positively correlated with habitat quality (Figure S4). Those sensitive soil quality indicators (e.g., soil pH, TN, and BD) adjusted plant nutrient absorption, soil element dissolution, and microbial community diversity, which jointly regulate ecosystem function and stability [64][65][66][67]. BRT models showed that MAT had the most considerable contribution to the habitat quality in high-level zones, which largely support previous findings [40].…”
Section: Drivers Of Habitat Quality Patternssupporting
confidence: 81%
“…We found that climate favorably mainly affected habitat quality by regulating the soil physical and chemical properties (Figures 4-6). Climate conditions influence landscape patterns, such as altering soil element concentration or moisture [64,75]. Notably, climate conditions had direct negative effects on habitat quality, and the influence pathway coefficients were higher in medium-level zones than in high-level zones across five periods (β = −0.1764, −0.2656, −0.2105, −0.2547, and −0.2925, respectively).…”
Section: The Driving Paths Of Habitat Quality Patternsmentioning
confidence: 99%
“…2020 which differentiates their absolute concentration and relative proportions of elements in each plant (BOTHE; SLOMKA, 2017). Calcium (Ca) is an intermediate micronutrient that, when found in excess or deficient, may be detrimental to the biochemical functions and growth of the plant, besides modifying soil pH and cation exchange capacity (REN et al, 2019).…”
Section: Morphological Analysis -Sem and Edsmentioning
confidence: 99%
“…At larger scales, the effect of climate on soil metal elements variations will be enhanced. For instance, Ren et al [22] concluded that the variations of metal elements were mainly influenced by longitude, pH, mean annual temperature and precipitation after analyzing over 50 elements based on 9830 topsoil samples across an area of 39000 km 2 in southeast China. Martin et al [23] reported that soil elements variations were closely linked to variations of source geology, soil type, climate and topography based on a database of the regional geochemical baseline soil survey in southern New Zealand.…”
Section: Introductionmentioning
confidence: 99%